Covid-19, online workshops, and the future of intellectual exchange. - Davies, Aled; Seaton, Andrew; Tonooka, Chika; White, Jessica (Rethinking History, 2021)
Covid-19 disrupted the fabric of academic collaboration. Scholars cancelled or delayed in-person talks, seminars, and conferences in an effort to reduce transmission of the virus. In many instances, the academic profession turned to various online platforms to share ideas. What are the possible long-term consequences of this development? Drawing on the experience of organizing an online workshop for early career researchers in modern British history, this article argues that virtual seminars and conferences should become a permanent part of intellectual exchange. This article provides practical guidance to others seeking to establish similar projects within and beyond the historical profession. It uses survey material from workshop presenters and attendees to assess the challenges and merits of using online platforms, and then discusses their longer term significance. Despite some drawbacks in their operation, online platforms offer advantages that include widening participation and responding to the climate crisis. Virtual collaboration facilitates the participation of scholars normally excluded from central field discussions due to location, expense, or institutional status, and it also furthers global scholarly interactions without generating a significant carbon footprint. This article argues that rather than a temporary stop-gap during a pandemic, online seminars present new opportunities for the future of collaboration if embedded as part of a mix with of in-person events. In its conclusion, it presents five proposals for improving virtual collaboration in the future.